2019
DOI: 10.1002/bkcs.11864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight of Poly(tetramethylene glycol) on Waterborne Polyurethane Dispersion Coating Gloss

Abstract: FE‐SEM images of different WPU coating surfaces with different gloss values at 60°

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Regarding the effect of the molecular weight of the polyol, Bhattari et al [ 16 ] prepared WBPU from polytetramethylene glycols (PTMGs) of different molecular weights and reported that the average size of the particles increased from 860 nm to 1355 nm for PTMGs of molecular weights of 1000 and 2000 Da, respectively. Thus, other conditions being equal, the increase in the length of the chain diol led to the increase in the average particle size of the WBPU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of the molecular weight of the polyol, Bhattari et al [ 16 ] prepared WBPU from polytetramethylene glycols (PTMGs) of different molecular weights and reported that the average size of the particles increased from 860 nm to 1355 nm for PTMGs of molecular weights of 1000 and 2000 Da, respectively. Thus, other conditions being equal, the increase in the length of the chain diol led to the increase in the average particle size of the WBPU.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, large particles are used when rapid drying is needed, while small particles lead to longer drying times but allow the penetration of the PU in the substrate, which could be essential in some applications [ 15 ]. The structural molecular characteristics of the polyol, its functionality and molecular weight, the nature, characteristics, and concentration of the internal emulsifier, and the ratio of isocyanate to hydroxyl groups are factors that affect the properties of the dispersions and also of the final films [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the incompatibility 13 of the matting agents with organic resins and precipitation problems in the coating layer, the matting agents may be difficult to disperse, reducing the mechanical properties of the cured coating film. 14 As for the self-matting resin, it is a chemical extinction method without any matting agents, and the rough surface is generated by the resin itself. 15 The objective of this strategy is to obtain large polymer particles by adjusting the weight ratio of hard/soft monomers, 16 and introducing hydrophilic units.…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of low-gloss material, self-matting waterborne polyurethanes usually have wider particle distribution, where large particles can play a role similar to matting agents, and small particles will impart better adhesion to the coating film [12][13][14][15]. Since no matting agent was contained in the dispersion, the film performance can be greatly improved, especially in the anti-scratch property.…”
Section: Introductionmentioning
confidence: 99%